Current status of acute rheumatic fever and heart disease in South Africa: Is it on fire, dead, or smouldering? - Cilliers, A (SA Heart Journal, 2025)
Rheumatic heart disease (RHD) is the most common acquired heart disease in people aged under 25 years. It affects an estimated 55 million people worldwide and claims approximately 360 000 lives each year, mostly from low- to middle-income countries.(1) RHD results from damage to heart valves caused by one or several episodes of acute rheumatic fever (ARF), which is a complex autoimmune inflammatory reaction to a throat infection caused by the group A β-haemolytic Streptococcus (GAS) organism in genetically susceptible individuals, most often during childhood. It is preventable through controlling the spread of GAS by addressing poverty and overcrowding, and prompt treatment of streptococcal throat infections with antibiotics.(1) Despite RHD’s eradication in many parts of the world, it remains prevalent in sub-Saharan Africa, the Middle East, Central and South Asia, the South Pacific, and among immigrants and older adults in high-income countries (HIC), especially indigenous peoples.(1) RHD epidemiology in Africa, where it remains an important health problem, is largely unknown and poorly documented. Prevalence rates vary in relation to poverty, limited education, awareness, and inadequate healthcare infrastructure.(2)